Update on Food protein-induced enterocolitis syndrome (FPIES) - Calvani , Mauro; Anania, Caterina; Bianchi, Annamaria; D'Auria, Enza; Cardinale, Fabio; Votto, Martina; Martelli, Alberto; Tosca, Mariangela; Chiappini, Elena; Brambilla, Ilaria; Miraglia Del Giudice, Michele; Caffarelli, Carlo (Acta Biomedica Atenei Parmensis, 2021)
Food protein-induced enterocolitis syndrome (FPIES) is a non-IgE mediated food allergy (FA) characterized by delayed and severe gastrointestinal symptoms that typically occurs within the first year of life. Many aspects of this pathology are currently unclear. FPIES is classified as a non-IgE immune-mediated FA in which the immune response is thought to act mainly through cell-mediated mechanisms. In patients with FPIES, the symptom pattern is determined by the frequency and dose of food allergen in the diet. Diagnosis of FPIES may be difficult, mainly due to the lack of specific biomarkers to confirm or exclude the diagnosis. FPIES is a clinical diagnosis, mainly based on clinical features which, although not specific, are reproducible every time the patient takes the food. Different diagnostic criteria of FPIES were published over time in the literature. The present narrative review aims to analyze the current clinical evidence in epidemiology, pathophysiology, diagnosis, and management of this condition.